Quantifying the Matrix Metalloproteinase 2 (MMP2) Spatially in Tissues by Probe via MALDI Imaging Mass Spectrometry - Yu, Daojiang; Lai, Peng; Yan, Tao; Fang, Kai; Chen, Lei; Zhang, Shuyu (Frontiers in Chemistry, 2021)
As a matrix metalloproteinase, the abnormal expression of MMP2 is associated with multiple biological processes including tissue remodeling and cancer progression. Therefore, spatial analysis and imaging of MMP2 protein in tissues can be used as an important approach to evaluate the distribution and expression of MMP2 in complex environment tissues, which can help the diagnosis and treatment of different diseases including tissue or organ injuries. and the evaluation of prognosis. However, MMP2 is difficult to image in MALDI TOF mass spectrometry. We designed a specific MMP2 probe that closely binds to MMP2 protein in tissue and has an isotope matrix on the other end of the probe, which can assist in enhancing the probe signal in mass spectrometry and can accurately quantify MMP2 protein. Based on this, we used the probe to assist tissue MALDI TOF imaging to determine the spatial expression of MMP2 in the tissue. This approach may help to study the influence of multifunctional proteases on the degree of malignancy in vivo.